The impact of beneficiaries in Mambusao of Community Economic Ventures a Microenterprise Development Strategy - Panes, Viviano S.
The Community Economic Venture is a Micro-enterprise Development strategy of World Vision Development Foundation for poverty alleviation. Its principles includes; sustainability, accountability, human resource development, technological development, and efficient management. Its implementation was pioneered in Bohol and expansion was started in Capiz in year 2000, particularly in Jamindan and Mambusao. Its strategy of selecting and screening of beneficiaries that includes track records, experience in micro-enterprises, existing owner of micro-enterprise proved effective. Moreover, its strategy of providing capital and technical assistance, proved needed and useful for the beneficiaries. The impact of the program to its beneficiaries was not limited only to increase in income, but also improved relationships with community and family members, development of values and attitudes such as fear in God, honesty, diligence, responsible, accountability, industry and hardworking. Moreover, there were enhanced skills on micro-enterprise management, making of project proposals, selecting of a profitable enterprises and improved customer relationships. This benefits derived from community Economic Ventures interlink with each other to make the impact to beneficiaries lasting and sustainable.